2011
DOI: 10.1007/s11102-011-0297-0
|View full text |Cite
|
Sign up to set email alerts
|

MGMT immunoexpression in adamantinomatous craniopharyngiomas

Abstract: At present, no effective medical treatment exists for recurrent and aggressive craniopharyngiomas that are resistant to conventional therapies, including surgery and adjuvant radiotherapy. Temozolomide is an alkylating chemotherapeutic agent used routinely in the management of high grade gliomas. The response to temozolomide is suggested to be dependent on the tumoral expression of O-6 methylguanine DNA methyltransferase (MGMT). Evidence supports that low MGMT immunoexpression correlates with positive response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The majority of adamantinomatous craniopharyngiomas exhibit zero to minimal expression of O-6 methylguanine DNA methyltransferase (MGMT), which confers a likely positive response to temozolomide treatment, an agent already being used for other brain tumors. 100 Similarly, tamoxifen has been shown to inhibit craniopharyngioma cell proliferation via inhibition of ADAM-like decysin 1 (ADAM-DEC1) expression, which is limited only to adamantinomatous craniopharyngioma cells and not normal brain tissue. 95 Though associated with significant toxicities and pending validation in animal models of craniopharyngioma, both of these drugs may potentially serve as adjuvant therapies for those tumors resistant to radiation or individuals in whom surgery is contraindicated.…”
Section: Future Directionsmentioning
confidence: 99%
“…The majority of adamantinomatous craniopharyngiomas exhibit zero to minimal expression of O-6 methylguanine DNA methyltransferase (MGMT), which confers a likely positive response to temozolomide treatment, an agent already being used for other brain tumors. 100 Similarly, tamoxifen has been shown to inhibit craniopharyngioma cell proliferation via inhibition of ADAM-like decysin 1 (ADAM-DEC1) expression, which is limited only to adamantinomatous craniopharyngioma cells and not normal brain tissue. 95 Though associated with significant toxicities and pending validation in animal models of craniopharyngioma, both of these drugs may potentially serve as adjuvant therapies for those tumors resistant to radiation or individuals in whom surgery is contraindicated.…”
Section: Future Directionsmentioning
confidence: 99%
“…Rodriguez et al showed that there was no significant correlation between MGMT expression and methylation, and no significant survival difference was observed between patients whose tumours were negative versus those whose tumours were positive for MGMT protein, as ascertained by immunohistochemistry (25). Also, in a study concerning craniopharyngiomas, Zuhur et al suggest that a high proportion of adamantinomatous craniopharyngioma express a low level of MGMT (26). In studies of pituitary adenomas, the expression of MGMT has no associations with the aggressiveness or relapse of pituitary adenomas (27,28).…”
Section: Invasiveness and Nfpamentioning
confidence: 99%
“…(WHO) classification, they often behave as aggressive tumors and cause significant mortality and morbidity (19,32). Malignant transformation of craniopharyngiomas either after radiotherapy or without previous radiotherapy has also been reported (15).…”
Section: Zuhur Ss Et Al: Immunohistochemical Expression Of Erbb2 In mentioning
confidence: 99%